Challenges of cross-border cooperation in the Greater Region: Interviews with relevant actors - Gerd-Rainer Damm (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This paper presents and analyses interviews held with decision-makers and actors involved in cross-border cooperation in the Greater Region, exploring the difficulties and constraints of the collaboration. In addition to problems caused by the different languages, administrative cultures and variations in the tasks and jurisdictions of the individual partners, the organisation of the Greater Region is also mentioned as a hindrance. Yet many difficulties concerning cooperation are minimised and in some cases overcome by the high level of commitment of the individuals active in crossborder cooperation. The paper concludes with recommendations to improve the working methods of cross-border cooperation.
urn:nbn:de:0156-40970565; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Importance of cross-border cooperation in the Greater Region; important projects; language skills; administrative cultures; effectiveness of the committees; steps to improve cross-border cooperation